Mere moral beliefs aren't sufficient to determine pro-social behaviors! A moderated mediation framework tested in healthcare settings based on Belief in Self-Determinism (BSD) Theory - Muhammad Ali Asadullah; Tabassum Iqbal; Ali Haj Khalifa; Sajid Haider (Acta Psychologica)
Healthcare professionals may frequently violate organizational policies to deal with ethical dilemmas challenging quality of patient care. However, healthcare professionals need strong moral foundation to justify such violation of organizational policies. This study emphasized on morality as one of the social factors nurturing individual characters embodying prosocial violation as explained by ‘Belief in Self-Determinism (BSD) Theory.’ Building on moral perspective of prosocial behaviors, this study explains that mere moral beliefs are insufficient to drive pro-social behaviors at the workplace until they are integrated with moral attitudes. This study tested a mechanism to explain how moral courage strengthens the effect of moral conviction on prosocial rule-breaking (PSRB) behaviors of healthcare professionals conditional to their professional experience. A sample of 129 doctors serving in public sector hospitals in Pakistan demonstrated that moral courage strengthens the role of moral conviction in pro-social rule-breaking behavior. The study also found that the mediating role of moral courage between moral convictions and pro-social rule-breaking differs across different levels of professional experience. Particularly, the meditating role of moral courage between moral convictions and prosocial behaviors reduces with the increase in professional experience. This study offers some important implications for healthcare professionals to regulate healthcare professionals' prosocial based on their moral beliefs, moral attitudes, and professional experience.